(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ulilalbab AR, Widinugraheni S, Masanto, Subandiyah S, Wibowo A. 2022. Expression of SIX1b and SIX1c effector genes and banana resistance genes during Foc TR4 infection on banana cultivars. Biodiversitas 23: 5314-5322. The relative expression SIX1 genes isolates of Foc TR4 and banana resistance genes have not been intensively studied. This study aimed to determine the expression of SIX1 genes of Foc TR4 and banana resistance genes. Twelve Foc TR4 isolates were collected from several regions in Indonesia. DSI analysis was performed to categorize their virulence levels. The representative Foc TR4 isolates from different virulence levels were artificially inoculated on the Musa acuminata Colla Cavendish subgroup and cv. Barangan and incubated for 48, 72, and 96 HPI. The expressed genes were quantitatively analyzed using the qPCR technique using primers to amplify SIX1b, SIX1c, chitinase, and PR-protein 1 genes. The results categorized the virulence of Foc TR4 isolates into moderate, virulent, and high virulent. The isolates of KJG and Batu-4 were selected for gene expression study representing moderate and high virulent groups, respectively. The results of in planta assay found that the expression of SIX1b, SIX1c, chitinase, and PR-protein1 was upregulated on the inoculated plants during the incubation period. However, the expression of these genes was increasingly upregulated in both bananas at early-stage inoculation. We assumed that plant defense genes of bananas might actively encounter the common virulence mechanisms of Foc TR4 at the initial stage of inoculation.